Long-term pulmonary complications in sulfur mustard-exposed patients: gene expression and DNA methylation of OGG1 - Mohammad Saber Zamani; Tooba Ghazanfari (BioImpacts)
Introduction: It is well established that tissues exposed to sulfur mustard (SM) generate high levels of reactive oxygen species. This leads to oxidative stress and, ultimately, damage to DNA molecules over the course of time. Additionally, SM, through its alkylating effects, is capable of directly damaging DNA on its own. In cells, these damages trigger a variety of DNA repair pathways, including the base excision repair (BER) pathway. Even so, in the long run, it remains unclear how the BER repair pathways will react. Methods: The purpose of this study was to assess the promoter DNA methylation and the mRNA expression of 8-oxoguanine glycosylase (OGG1), one of the key components of the BER pathway, in patient PBMCs that were exposed to SM 27 years ago using methylation-sensitive high resolution melting and qPCR. The study was conducted on three groups of participants exposed to SM with mild (n = 20), moderate (n = 24), and severe (n = 20) lung complications. Results: Our results showed significant OGG1 mRNA overexpression was observed in moderate groups compared to mild groups (P = 0.036). DNA methylation was also altered in mild-moderate and moderate-severe groups (P < 0.0001 and 0.023, respectively). Although aging was significantly associated with OGG1 mRNA expression, promoter DNA methylation of OGG1 was not associated with its mRNA expression. Conclusion: This study revealed differences in OGG1 mRNA expression and DNA methylation among the severity groups of long-term pulmonary complications associated with SM exposure. However, there was no correlation between OGG1 DNA methylation and mRNA expression. Therefore, it appears that other mechanisms may be contributing to the dysregulation of OGG1 mRNA expression.